Co to jest medium? - Kozłowski, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
What is a Medium? At the beginning the author expresses his opinion that there is a national confusion which nowadays prevails about the nation of medium. His explications, in which he reminds his readers about the indirectness of media communication, are of historical character and expose numerous examples of notional abuse. One of the these states that without defining, in the broadest possible way, the notion of medium, which is a crucial one for media studies, it appears tha any systematic scientific reflection is impossible. As a remedy for the notional confusion, acceptance of the realistic definition of medium which was worked out by Werner Faulstich and based on the theoretical concept of Urlich Saxer („media are systems which solve problems”) is suggested. Therefore, that definition, four dimensions of which define the bases of empirical media studies, means the symbolic „patricide” of the main founder of modern media studies Marshall McLuhan and makes empirical, functional history and theory of the media possible.